Work-practice changes associated with an electronic emergency department whiteboard. (March 2013) - Hertzum, Morten; Simonsen, Jesper
Electronic whiteboards are introduced at emergency departments (EDs) to improve work practices. This study investigates whether the time physicians and nurses at an ED spend in patient rooms versus at the control desk increases after the introduction of an electronic whiteboard. After using this whiteboard for four months nurses, but not physicians, spend more of their time with the patients. With the electronic whiteboard, nurses spend 28% of their time in patient rooms and physicians 20%. Importantly, the changes facilitated by the electronic whiteboard are also dependent on implementation issues, existing work practices and the clinicians' experience. Another change in the work practices is distributed access to whiteboard information from the computers in patient rooms. A decrease in the mental workload of the coordinating nurse was envisaged but has not emerged. Achieving more changes appears to require an increase in whiteboard functionality and a firmer grip on the implementation process.